IDDF2020-ABS-0117 Gut microbiota associated with the sensitivity of hepatocellular carcinoma to sorafenib. (18th November 2020) - Lian, Weibin; Li, Haiwei; Chen, Zhangran; Lian, Yifan
Abstract : Background: Little is known about the relationship between alteration of gut microbiota and the sensitivity of hepatocellular carcinoma (HCC) to sorafenib. We performed a comparative study of gut microbiota composition between sorafenib-resistant HCC patients (R group, n=10) and sorafenib sensitive HCC patients (S group, n=10). Methods: Twenty patients were classified into two groups based on the sensitivity of hepatocellular carcinoma to sorafenib within 12 months of post-sorafenib treatment. Treatment response was assessed using modified response evaluation criteria in solid tumors (mRECIST) criteria. After sorafenib treatment, the fecal samples were analyzed using 16S rRNA gene sequencing and LC-MS-based metabolomics approach. Results: Compared with the R group, significant gut microbiota alterations were associated with the sensitivity of HCC to sorafenib. The results showed that the S group had higher Faecalibacterium, Enterococcus and Veillonella abundance while the R group had higher levels of Lactobacillus and Prevotellaceae. Additionally, the S group had a higher bacterial network complexity compared with the R group. Moreover, both Salbutamol and Glyclopyramide correlated positively with Anaerostipes. Conclusions: These observations will lead to a better understanding of the relationship between alteration of gut microbiota and the sensitivity of HCC to sorafenib. Gut microbiota and microbe-associated metabolites can be used as diagnostic biomarkers in therapeutic explorations.